Role of chest X-ray in tuberculous cervical lymphadenitis (Journal of Dhaka Medical College, 2015)
Tuberculous cervical lymphadenitis is not an uncommon entity when it comes to otolaryngology practice in Bangladesh. This study was done in the department of ENT and Head Neck Surgery, Dhaka Medical College Hospital, Dhaka, from January 2012 to January 2013 and was designed to find out chest x-ray abnormalities in apparently chest asymptomatic confirmed tuberculous cervical lymphadenitis without associated diseases. The diagnosis of tuberculous cervical lymphadenitis was confirmed by fine needle aspiration cytology (FNAC) and/or smear for acid-fast bacillus, and chest x-ray (PA view) was done in all confirmed cases (n=183). Normal chest x-ray was found in 132 cases (72.13%) and abnormal chest x-ray in 51 cases (27.87%). Pulmonary infiltration, the commonest radiological finding was detected in 32 cases (17.49%), hilar enlargement in 17 cases (9.29%), right paratracheal opacity in 2 (1.09%), obliteration of costophrenic angles in 3 cases (1.64%) and miliary mottling in one case (0.55%). Upper zonal predominance of lung parenchymal infiltrations was noted in 12.57% and right lung involvement in 16.39%. Single zone was affected in 9.84% cases and multiple zones were involved in 7.65% cases. We observed right hilar enlargement in 6.56%, left hilar lymphadenopathy in 4.37% and bilateral hilar lymphadenopathy in 2.73% cases. We concluded that routine chest x-ray should be done in all tuberculous lymphadenitis before categorization and starting of treatment. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21521 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 125-128